Thermal energy storage using phase-change material in evacuated-tubes solar collector - Akthem Mohi Al-Abdali; Handri Ammari (AIMS Energy, 2022)
The use of phase change materials in solar thermal collectors improves their thermal performance significantly. In this paper, a comparative study is conducted systematically between two solar receivers. The first receiver contains paraffin wax, while the other does not. The goal was to find out to which degree paraffin wax can enhance the energy storage and thermal efficiency of evacuated tubes solar collectors. Measurements of water temperature and solar radiation were recorded on a few days during August of 2021. The experimental analysis depended on two stages. The first stage had a flow rate of 7 L/hr, and the second stage had no flow rate. A flow rate of 7 L/hr gave an efficiency of 47.7% of the first receiver with phase-change material, while the second conventional receiver had an efficiency rate of 40.6%. The thermal efficiency of the first receiver during the day at which no flow rate was applied was 41.6%, while the second one had an efficiency rate of 35.2%. The study's significant results indicated that using paraffin wax in solar evacuated tube water-in-glass thermal collectors can enhance their thermal energy storage by about 8.6% and efficiency by about 7%. Moreover, the results revealed that the solar thermal collector containing paraffin wax had an annual cost of 211 USD/year. At the same time, the receiver's yearly fuel cost was 45 USD. Compared to an electrical geyser, the annual cost reached 327 USD, with an annual fuel cost equaled 269 USD. The first receiver's payback period was 5.35 years.